(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The Fergana Valley is one of the richest floristic regions in Central Asia; however, over the past 50 years, systematic inventory studies have been practically non-existent here. The lack of up-to-date data hampers the development of strategies for biodiversity conservation and sustainable use of plant resources. The aim of this article is to conduct a comprehensive inventory of vascular plants in the Fergana Valley, determine its current floristic richness, identify rare and endemic species, and assess the degree of anthropogenic impact on the flora. From 2018 to 2024, 428 route surveys were carried out, over 18,000 herbarium specimens were collected and processed, and collections from 12 herbaria were analyzed. A total of 3,784 species of vascular plants belonging to 794 genera and 128 families were identified. For the first time, 164 species were recorded for the valley, and the presence of 42 species previously considered extinct was confirmed. 218 endemic and sub-endemic taxa have been identified, with 312 species included in national Red Lists.